Pullwinding technique for realizing hybrid roving architecture in pultruded GFRP composites. (1st February 2023) - Liu, TianQiao; Feng, Peng; Tang, Juntian; Liu, Xing
Abstract: In this work, pullwinding technique is adopted to realize the hybrid roving architecture in pultruded GFRP composites so as to improve their transverse properties as well as the flexural performance of GFRP beams. First, small-scale material characterization tests and large-scale four-point bending tests were conducted to evaluate the mechanical performance of pullwound composites and the flexural behavior of pullwound box-beams. Second, analytical study was performed to calculate the strength and modulus of laminated plates with hybrid roving architectures. Then, finite element modeling was conducted to assess the strength and stability limit states of pullwound beams. The hybrid roving architecture could effectively reduce the material orthotropy, thus improving the transverse properties of GFRP composites as well as the flexural performance of GFRP beams. In the end, a design procedure is proposed to facilitate the design of roving architecture of pullwound composites to achieve the desired mechanical properties.